Constitutions, military force, and implications for German American relations - Kenneth B. Moss (Stiftung Wissenschaft und Politik (SWP), 2005)
The constitutional procedures and practices that governments have in place to declare war or to authorize the use of military force in an intervention significantly influence their ability to use armed force and to justify such action. For example, American Presidents often deploy military forces into hostile situations and subsequently seek votes in the U.S. Senate and House of Representatives to authorize this action. Such concentration of power in a President's hands allows for a degree of flexibility in using armed force that is not shared by the governments of some U.S. allies. In the latter, both a clearer political consensus and a prior parliamentary vote to authorize military intervention may be necessary before military forces are used. Such constitutional differences can amplify the issues that actually cause political disagreement tension between the U.S. and a friendly government. Indeed, the leeway American Presidents believe they have to use armed force may contribute to future disagreements over the appropriate and justifiable use of the military arm. (SWP Comments / SWP)
Keywords: 320